RESULTS OF THE STUDY OF THE CROUP ETIOLOGY IN CHILDREN AND EVALUATION OF INHALANT CORTICOSTEROID EFFICIENCY - G.G. Makhkamova; E.A. Shamansurova (Union of pediatricians of Russia, 2009)
Acute obstructive laryngitis (croup - J.05) is one of the pressing and insufficiently studied issues in pediatrics. Over recent years focus has been on the issues related to the treatment of this condition due to a relative incidence rate and severity of croup in children of minor age. A clinical and lab study has been undertaken to identify the etiological structure and evaluation of beclo methasone efficiency in 163 children aged 3 months to 5 years with croup. Results of the study have demonstrated that most often the etiological factor of croup is parainfluenza virus (56,1% of all cases), respiratory syncytial virus is revealed in 44,73% of all cases. Bacterial etiology of the disease have been found in 12,5% of children with the etiological agent being Haemophilus influenzae type b. Supplementation of the treatment for acute obstructive laryngitis of virus etiology with inhalant beclomethasone makes it possible to reduce the number of intubations, hence decrease the frequency of complications after invasive interventions and cut the length of hospital stay.Key words: Beclomethasone, acute obstructive laryngitis, children.